Ganzzahlige Darstellungen der zyklischen Gruppe von sechster Ordnung - Matuliauskas, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Матуляускас. Целочисленные представления циклической группы шестого порядкаA. Matuliauskas. Šeštos eilės ciklinės grupės atvaizdavimas sveikų skaičių matricomis